Effect of Salt Solutions on The Performance of "JAVA Citronella" - Singh, Omvir; Pal, B; Dadhwal, K S (Annals of Arid Zone, 2016)
Salt solutions viz., NaCl, CaCl2, MgCl2, NaHC03 and Na2C03 affected tillers/plant and herb yield of’ Java citronella’ (Cymbopogon martini). More than 30% herb yield reduction was recorded with Na2C03 in comparison to CaCl2, MgCl2, NaCl and Na2S04. Various salts also affected the chemical composition significantly in second harvest. Ionic nature of salt solutions affected nutrient uptake significantly and CaCl2 and MgCl2 were found to have more favourable dominating effect whereas, Na2CO3 the least.